Matriks SWOT Analysis of Sustainable Tourism Development in Bintan Regency After the Covid-19 Pandemic - Fatmasari, Nur Aisyah (CV. Austronesia Akademika, 2025)
Indonesia has several potentials that have been developed to accelerate tourism marketing after the Covid-19 pandemic, one of the areas in Bintan Regency, which is currently recovering the tourism sector where the potential for the strategic location of the area makes stakeholders have to complete various strategic efforts in mapping sustainable tourism. Sustainable tourism aims to maintain the stability of human and natural resources so that visiting tourists get an excellent tourism concept. This paper analyses the SWOT strengths, weaknesses, opportunities and threats to identify sustainable tourism development in Bintan Regency after the Covid-19 Pandemic. The research method uses a qualitative approach by collecting some secondary data, which is then processed into in-depth analysis material according to the current phenomenon. The analysis tool uses a triangulation model in the form of data, documents and findings based on observations which are then narrated in in-depth analysis results. The findings show that the SWOT matrix requires the concept of Border Cross Tourism as a policy strategy in formulating sustainable tourism. Then also by paying attention to the supervision and control stipulated in Ministerial Regulations (KEMENPAREKRAF) or Presidential Regulations (PERPRES) so that sustainable tourism development after the Covid-19 pandemic can be implemented in realizing 4 A tourism indicators consisting of Accessibility, Accommodation, Attraction, Activities and Amenities in maintaining tourism stability by involving foreign direct investment which has been regulated in standard operating procedures (SOP) which several neighbouring countries in the Bintan Regency area must obey.